2022
DOI: 10.1016/j.clim.2021.108911
|View full text |Cite
|
Sign up to set email alerts
|

Association of KIR gene polymorphisms with COVID-19 disease

Abstract: Background Natural killer (NK) cells play an essential role against viruses. NK cells express killer cell immunoglobulin-like receptors (KIRs) which regulate their activity and function. The polymorphisms in KIR haplotypes confer differential viral susceptibility and disease severity caused by infections. We investigated the association between KIR genes and COVID-19 disease severity. Methods 424 COVID-19 positive patients were divided according to their disease severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
1
20
1
Order By: Relevance
“…Moreover, this study also found a significant association between AA KIR-haplotypes and patients with severe COVID-19 disease compared to symptomatic-paucisymptomatic patients. In contrast to the Sardinian study, Bx genotypes were associated with COVID-19 patients in Soudhi Arabian population ( Hajeer et al, 2022 ). A study in Turkey revealed an association between COVID-19 and specific centromeric and telomeric halves of KIR haplotypes with HLA class I ligands ( Beksac et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Moreover, this study also found a significant association between AA KIR-haplotypes and patients with severe COVID-19 disease compared to symptomatic-paucisymptomatic patients. In contrast to the Sardinian study, Bx genotypes were associated with COVID-19 patients in Soudhi Arabian population ( Hajeer et al, 2022 ). A study in Turkey revealed an association between COVID-19 and specific centromeric and telomeric halves of KIR haplotypes with HLA class I ligands ( Beksac et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 88%
“…Only five studies have investigated the impact of KIR receptors on SARS-CoV-2 infection ( Beksac et al, 2021 ; Bernal et al, 2021 ; Lesan et al, 2021 ; Littera et al, 2021 ; Hajeer et al, 2022 ). In contrast to our findings, a study with a small number of 16 patients from the German Caucasian cohort revealed that patients with activating KIR2DS5 were recovered from COVID-19 in a shorter time than the individuals negative for the KIR2DS5 gene ( Lesan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of SARS-CoV-2, the KIR AA genotype was associated to a severe COVID-19 disease, in particular, the KIR2DS4 was the most significantly associated with severity, followed by KIR3DL1. Interestingly, the AA genotype encodes for various inhibitory KIRs and only one activating KIR (178).…”
Section: Host Genetic Factorsmentioning
confidence: 99%
“…Further protection could derive from interactions between killer-cell immunoglobulin-like receptors (KIRs), expressed on the surface of natural killer (NK) cells and their cognate human leukocyte antigen (HLA) Class I ligands ( 20 , 21 ). A recent study performed on the population of central southern Sardinia showed that KIR2DS2 in combination with HLA-C alleles of the C1 group exerts a potent protective effect against the adverse outcomes of COVID-19 ( 22 ).…”
Section: Introductionmentioning
confidence: 99%